Helicobacter pylori in peptic ulcer disease: pathogenesis, gastric microbiome, and innovative therapies - Sourav Pal; Junaid Ahamed Laskar; Biprojit Bhowmick; Khokan Bera (Bulletin of the National Research Centre)
Abstract The gastrointestinal (GI) system is fundamental to human health, managing digestion, nutrient absorption, and waste elimination. Among the pathogens that disrupt this system, Helicobacter pylori (HP) stands out as a major contributor to GI disorders, including gastritis, peptic ulcers, and gastric cancer. Given the well-documented and escalating crisis of antibiotic resistance, which undermines the efficacy of conventional antibiotic therapies, there is a pressing need to explore alternative treatment approaches. This review examines the colonization and the pathophysiology of HP infection, as well as the molecular mechanisms underlying its associated diseases. Furthermore, this study investigates novel treatments, emphasizing herbal alternatives like curcumin and green tea, which are well-known for their anti-inflammatory and antioxidant abilities, as well as marine-based remedies like fucoidan and chitosan, which are abundant in bioactive components with antimicrobial and anti-cancer qualities. Their diverse bioactive constituents offer broad-spectrum health benefits, and the absence of observed cross-resistance enhances their therapeutic appeal. This review seeks to provide a holistic approach to managing HP-related disorders by including insights into the digestive system and emerging strategies for treatment.